Innovation of Digital Marital Education using Waterfall Approach - Iqbal Maulana; Tutik Khotimah; Hanik Hidayati (International Journal of Informatics and Computation, 2025)
Marital education, traditionally delivered through in-person workshops or counseling sessions, faces challenges related to accessibility, engagement, and customization. This paper explores the innovation of digital marital education by implementing the Waterfall approach to systematically design and develop a mobile application tailored for couples. The Waterfall methodology, known for its structured, step-by-step development process, ensures that the design of the app is meticulously planned and executed with clear objectives for each stage, from initial requirements gathering to final deployment. The proposed application integrates interactive modules on communication, conflict resolution, and relationship-building, along with features designed to increase user engagement, such as self-assessments and feedback loops. Through the Waterfall approach, each development phase is thoroughly documented, ensuring a user-centered design that addresses usability and content relevance. The effectiveness of the application is evaluated through a series of testing phases, which include feedback collection from target users to ensure the app meets the educational needs of couples. The findings suggest that the Waterfall approach, while rigid, results in a highly structured, reliable system for the development of a marital education tool, with positive implications for enhancing relationship quality and communication. Future work will explore iterative improvements and the potential integration of adaptive learning techniques.